2009
DOI: 10.1007/s10535-009-0080-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sucrose application, minerals, and irradiance on the in vitro growth of Cistus incanus seedlings and plantlets

Abstract: To study the effect of sucrose on the sink-source relationship in in vitro-grown plants, Cistus incanus seedlings and plantlets were grown horizontally in a two-compartment Petri dish (split dish), with the root system in one compartment and the shoot in the other. Shoots and roots were exposed to different sucrose concentrations (0 -30 g dm -3 ), two irradiance levels (25 and 160 µmol m -2 s -1 ) and the presence or absence of a minimum medium containing minerals and vitamins (M medium). Root and shoot biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The authors suggest that the characteristics may modify the phenotypic response of examined genotype depending on the composition of used medium, which makes some components of the medium unavailable to plants. Other factors affecting seedling growth in a mature embryo culture may include embryo length (Monnier, 1990) and C:N ratio (Malamy and Ryan, 2001;Mills, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that the characteristics may modify the phenotypic response of examined genotype depending on the composition of used medium, which makes some components of the medium unavailable to plants. Other factors affecting seedling growth in a mature embryo culture may include embryo length (Monnier, 1990) and C:N ratio (Malamy and Ryan, 2001;Mills, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The poor acclimatization of somatic embryoderived plantlets is, however, a serious handicap (Moon et al 2006). Recently, a photoautotrophic propagation methodology was applied to improve the physiological, anatomical, and morphological characteristics of in vitro grown plantlets (Mills 2009). Plants grown by this method showed better acclimatization to ex vitro transplantation (Kozai 1991a,b, Ziv 1995, Lian et al 2002, Zobayed et al 2004, Nguyen and Kozai 2005.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Culture conditions sustaining high multiplication rates have a major effect on the growth and physiology of developing plantlets (Ziv 1995). Leaves are the major organ affected during plantlet growth in vitro (Mills 2009); although the stem is also affected, it has (unless very malformed) a smaller immediate impact on plant water stress and ex vitro survival. In this study, the plantlets, grown under the photoautotrophic condition with forced ventilation, possessed more leaves (2.8 per plant) and larger leaf area (18.9 cm 2 ) than those cultured under the conventional and the photoautotrophic (without ventilation) conditions (Table 1, Fig.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…At distances above 1.0 cm, plant development was getting lower again. Mills (2009) has stated that sucrose in the growth medium improves biomass production and photosynthetic activity by increasing leaf area. Mingozzi and Morini (2009) have reported that physical microenvironment affects in vitro regeneration significantly.…”
mentioning
confidence: 99%